SQL all-in-one for dummies - Taylor, Allen G.; Blum, Richard 1962- (--For dummies, 2024)
The most thorough SQL reference, now updated for SQL:2023 SQL All-in-One For Dummies has everything you need to get started with the SQL programming language, and then to level up your skill with advanced applications. This relational database coding language is one of the most used languages in professional software development. And, as it becomes ever more important to take control of data, there's no end in sight to the need for SQL know-how. You can take your career to the next level with this guide to creating databases, accessing and editing data, protecting data from corruption, and integrating SQL with other languages in a programming environment. Become a SQL guru and turn the page on the next chapter of your coding career. Get 7 mini-books in one, covering basic SQL, database development, and advanced SQL concepts Read clear explanations of SQL code and learn to write complex queries Discover how to apply SQL in real-world situations to gain control over large datasets Enjoy a thorough reference to common tasks and issues in SQL developmentThis Dummies All-in-One guide is for all SQL users--from beginners to more experienced programmers. Find the info and the examples you need to reach the next stage in your SQL journey.